Comparison of GC–MS, GC–MRM-MS, and GC GC to characterise higher plant biomarkers in Tertiary oils and rock extracts - Eiserbeck, Christiane; Nelson, Robert; Grice, Kliti; Curiale, J; Reddy, Christopher (Pergamon-Elsevier Science Ltd, 2012)
Higher plant biomarkers occur in various compound classes with an array of isomers that are challenging to separate and identify. Traditional one-dimensional (1D) gas chromatographic (GC) techniques achieved impressive results in the past, but have reached limitations in many cases. Comprehensive two-dimensional gas chromatography (GC × GC) either coupled to a flame ionization detector (GC × GC–FID) or time-of-flight mass spectrometer (GC × GC–TOFMS) is a powerful tool to overcome the challenges of 1D GC, such as the resolution of unresolved complex mixture (UCM). We studied a number of Tertiary, terrigenous oils, and source rocks from the Arctic and Southeast Asia, with special focus on angiosperm biomarkers, such as oleanoids and lupanoids. Different chromatographic separation and detection techniques such as traditional 1D GC–MS, metastable reaction monitoring (GC–MRM-MS), GC × GC–FID, and GC × GC–TOFMS are compared and applied to evaluate the differences and advantages in their performance for biomarker identification. The measured 22S/(22S + 22R) homohopane ratios for all applied techniques were determined and compare exceptionally well (generally between 2% and 10%). Furthermore, we resolved a variety of angiosperm-derived compounds that co-eluted using 1D GC techniques, demonstrating the superior separation power of GC × GC for these biomarkers, which indicate terrigenous source input and Cretaceous or younger ages. Samples of varying thermal maturity and biodegradation contain higher plant biomarkers from various stages of diagenesis and catagenesis, which can be directly assessed in a GC × GC chromatogram.The analysis of whole crude oils and rock extracts without loss in resolution enables the separation of unstable compounds that are prone to rearrangement (e.g. unsaturated triterpenoids such as taraxer-14-ene) when exposed to fractionation techniques like molecular sieving. GC × GC–TOFMS is particularly valuable for the successful separation of co-eluting components having identical molecular masses and similar fragmentation patterns. Such components co-elute when analysed by 1D GC and cannot be resolved by single-ion-monitoring, which prevents accurate mass spectral assessment for identification or quantification.